Evaluation of Existing Damage Patterns and Seismic Assessment of Historical Davutpasa Barracks via Operational-Modal Analysis - Gani, Emre; Erdogan, Yildirim Serhat; Kocak, Ali (ASCE-AMER SOC CIVIL ENGINEERS, 2020)
The seismic assessment of heritage buildings has great importance in terms of preservation and sustainability due to their priceless inheritance. In general, the material properties used in the construction of heritage buildings, static and dynamic effects, to which they are exposed, and the existing structural damages are uncertain. Additionally, heterogeneous walls are often assumed to be homogeneous and many assumptions are made for the boundary conditions to reduce the computational burden in numerical analyses. In order to handle these uncertainties, operational modal analysis (OMA) has been successfully applied to moderate historical constructions. In this study, the seismic behavior of a large-scale historical building, which is located in Istanbul/Turkey and known as the Davutpasa Barracks is discussed. At first, an initial numerical model was created and calibrated using the data provided by OMA and in-situ observations. Afterwards, the seismic analyses of the barracks were performed using the initial and the calibrated model. The stress distributions and the displacement time histories of the building were examined and the critical sections of the barracks were estimated. The results have shown that the existing damages arise from both the seismic effects and the ground settlements. Additionally, it was revealed that the corridor facade walls and the corners, where the two very long monoblock building sections engage, are sensitive to seismic excitations.
Keywords: Earthquake behavior; Condition assessment; Finite-element analysis; Historical buildings; Masonry structures; Operational modal analysis; Model calibration; DYNAMIC IDENTIFICATION; MASONRY; VULNERABILITY; RESTORATION; BUILDINGS; HERITAGE; BASILICA; TOWER; Construction & Building Technology; Engineering